Experience with Zone 2 Arch Replacement Followed by Thoracic Endovascular Aortic Repair - Dhanekula, Arjune; DeGraaff, Bret; Flodin, Rachel; Reimann-Moody, Anne; Garza, Manuel De La; Zettervall, Sara; Shalhub, Sherene; Sweet, Matthew P.; Burke, Christopher R.; DeRoo, Scott (AORTA, 2024)
Background Transverse open aortic arch replacement remains a complex operation. A simplified arch replacement into zone 2, with debranching the head vessels proximally, creates a suitable landing zone for future endovascular repair and is increasing in popularity as of late. Still, limited data exist to assess contemporary rates of morbidity and mortality. Therefore, we aim to evaluate current outcomes for patients who underwent open zone 2 aortic arch replacement.Methods All patients who underwent zone 2 arch replacement at a single academic institution from January 2019 to June 2023 were assessed. Indication for operation was either aneurysmal disease (n = 37), acute aortic syndrome (n = 38), or residual arch/descending thoracic aorta dissection (n = 67). Patient demographics and operative characteristics were evaluated, and the frequency of subsequent thoracic endovascular aortic repair (TEVAR) was noted. Mortality and major morbidity were then assessed.Results A total of 142 patients underwent open zone 2 arch replacement. Median cardiopulmonary bypass, cross-clamp, and deep hypothermic circulatory arrest times for the entire cohort were 195, 122, and 36.5 minutes, respectively. Concomitant frozen elephant trunk was performed in 45.1% of the cohort (n = 64). In-hospital mortality was 7.8% (n = 11) for the entire cohort. Spinal cord ischemia occurred in 3.5% (n = 5); these patients all received frozen elephant trunks and had neurologic recovery by discharge. Stroke occurred in 9.2% (n = 13) of the study cohort. A total of 38.7% (n = 55) went on to get subsequent TEVAR, with median time to TEVAR of 52 days (8, 98.5).Conclusion Zone 2 arch replacement allows staged repair of the thoracic aorta and readily accommodates future TEVAR therapy. This option for the treatment of the aortic arch can be performed safely in a wide variety of patient pathologies. Given the safety of this operation, cardiac surgeons should utilize this approach more frequently.
Keywords: aorta; arch; TEVAR; landing zone; cardiac surgery; arch replacement